Louis Kriesberg: Pioneer in Peace and Constructive Conflict Resolution Studies - Kriesberg, Louis (Pioneers in Arts, Humanities, Science, Engineering, Practice, 2016)
XIX, 203 p. 19 illus., 16 illus. in color.